Hip physical examination extension loss and radiographic osseous findings in patients with low back pain and nonarthritic hips. Issue 4 (9th June 2022) - Feng, Richard; Hatem, Munif; Nimmons, Scott J.; Disantis, Ashley; Martin, RobRoy L.; Martin, Hal David
Abstract: The association between hip and spine abnormalities is frequent, and limitation in hip extension has been linked with low back pain. The purpose of this study was to assess the radiographic osseous findings in nonarthritic hips of patients with hip pain, low back pain, and limited hip extension. Ninety patients (92 hips) were included in this study. Hip extension was tested in the contralateral decubitus position with the hip in neutral abduction/adduction and neutral rotation. In sequence, hip extension was tested by adding passive abduction, followed by internal/external rotation of the hip. A hip extension limitation was defined as less than zero degrees of extension. Imaging studies were assessed for the following osseous morphologies: decreased ischiofemoral space (≤17 mm), increased femoral torsion (≥30°), decreased femoral torsion (≤5°), and posterior acetabular overcoverage. Fifty-seven out of 92 hips (62%) had at least one osseous imaging finding for limitation in hip extension: decreased ischiofemoral space (38/92, 41%), increased femoral torsion (5/92, 5%), decreased femoral torsion (24/92, 26%), and posterior acetabular overcoverage (21/92, 23%). Decreased ischiofemoral space, femoral torsional abnormalities, and/or posterior acetabular wall overcoverage are observed in imaging studies of most individuals with limitation of hip extension and low back pain.